2015
DOI: 10.1016/j.plefa.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of lard-enriched diet on tissues fatty acids composition and hypothalamic insulin actions

Abstract: Background: high saturated fat intake is positively correlated with mild chronic inflammatory conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…A previous report showed that myristic acid (C16:0) produced anxiolytic-like effects comparable to those of diazepam in male rats (Contreras et al, 2014 ). We have previously reported myristic acid as the most abundant fatty acid in the lard-enriched diet consumed by our animals (Dornellas et al, 2015 ). It has been shown that palatable foods, such as diets rich in sugar and lard, reduced signs of stress and anxiety in humans and animals (Finger et al, 2011 ; Singh, 2014 ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A previous report showed that myristic acid (C16:0) produced anxiolytic-like effects comparable to those of diazepam in male rats (Contreras et al, 2014 ). We have previously reported myristic acid as the most abundant fatty acid in the lard-enriched diet consumed by our animals (Dornellas et al, 2015 ). It has been shown that palatable foods, such as diets rich in sugar and lard, reduced signs of stress and anxiety in humans and animals (Finger et al, 2011 ; Singh, 2014 ).…”
Section: Discussionmentioning
confidence: 54%
“…The high-fat diets were prepared by adding, to the standard chow, 20% (w/w) fat, 20% (w/w) casein, 10% (w/w) sucrose, and 0.02% (w/w) butylated hydroxytoluene (Watanabe et al, 2010 ; Dornellas et al, 2015 ). The lard diet contained 2% soybean oil to ensure the adequate content of essential PUFAs (Reeves, 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…Energy intake was significantly higher in all high-fat diet groups (HFC, HFJ 0.25%, and HFJ 0.5%) due to the higher energy density of the diets than that in the C group. Body weight gain (Δ) in the HFC group was increased as expected, indicating that the high-fat diet model was efficient in inducing body weight gain even with short-term diet intake [ 18 , 19 ]. Interestingly, the body weight of rats in the HFJ 0.25% group did not differ from that in the C group, suggesting that low doses of juçara have a protective role against body weight gain and consequently obesity development.…”
Section: Discussionmentioning
confidence: 73%
“…The animals received their respective diets ad libitum, and diet consumption was measured to assess the calorie intake. The control group (C) received a rodent standard commercial diet, the high-fat diet model used was stablished by Dornellas [ 18 ] whereupon the main ingredient is the standard commercial diet with changes in the amount of fat. Juçara supplementation was done by mixing the powdered freeze-dried juçara pulp in the modified diet before pelleting.…”
Section: Methodsmentioning
confidence: 99%
“…The main problem with the methodology lies in the composition of the diets, as they differ not only in the addition of lard but also in the amount of casein (present only in the C and C+HF group); the amount of cornstarch (41 vs. 23.97 in the C and C+HF groups, respectively); and, most notably, the amount of sucrose provided to the animals. Even though their composition of lipids, proteins, and carbohydrates are similar, the high amount of lard does have an effect on hypothalamic insulin signaling [ 2 ]. Authors show in their Table that C and C+HF groups received 10 and 7.8 g of sucrose in the diet, while BB and BB+HF received 1.3 g and 0 g of sucrose, respectively.…”
mentioning
confidence: 99%